What constitutes effective feedback to postgraduate research students? The students’ perspective - East, Martin; Bitchener, John; Basturkmen, Helen (Journal of University Teaching and Learning Practice, 2012)
Many Western universities are experiencing considerable growth in the numbers of postgraduate research students, both local and international. This increase and diversification bring with them challenges for how to make these students’ research studies successful. In particular, what students may wish to receive by way of supervisor-student relationships, and feedback within those relationships, may differ from what supervisors give, thereby creating potential tensions in the relationship and hindering effective learning. This article looks at what research students report they receive by way of feedback from supervisors, and what they say they find most effective. Evidence from questionnaires (n = 53) and interviews (n = 22) is used to draw some conclusions about how effective feedback is conceptualised from the students’ perspective. Analysis includes similarities and differences in response for students who speak English as a first or additional language.